2019
DOI: 10.1680/jenge.16.00009
|View full text |Cite
|
Sign up to set email alerts
|

Microbial induced calcite precipitation by Sporosarcina pasteurii and Sporosarcina aquimarina

Abstract: Factors that influence microbially induced carbonate precipitation (MICP) include bacterial species, bacterial cell concentration and urea and calcium ion (Ca2+) concentrations for determining the most effective laboratory conditions for calcium carbonate (CaCO3) precipitation by Sporosarcina pasteurii and Sporosarcina aquimarina bacteria. In this study, the most effective laboratory conditions for MICP by S. aquimarina were 12·8 × 109 bacterial cells/ml, 0·25 M urea and 2 M calcium chloride (CaCl2). On the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The authors further demonstrated that the use of native bacteria at low flow rates results in even delivery of calcite precipitation points at or lower than 4% by weight of the soil sample. In summary [111], it is suggested that the bacterial cell density and urea and calcium ion concentrations are important factors for effective calcite precipitation via MICP processes.…”
Section: Availability Of Nucleation Sites (Bacterial Suspension Density)mentioning
confidence: 99%
“…The authors further demonstrated that the use of native bacteria at low flow rates results in even delivery of calcite precipitation points at or lower than 4% by weight of the soil sample. In summary [111], it is suggested that the bacterial cell density and urea and calcium ion concentrations are important factors for effective calcite precipitation via MICP processes.…”
Section: Availability Of Nucleation Sites (Bacterial Suspension Density)mentioning
confidence: 99%
“…The carbonate mineral percentage of the samples was determined by using an acid washing technique (Keykha et al 2018a). The soil samples were soaked into an acid solution (HCl 5 M).…”
Section: Uncon Ned Compressive Strength Testmentioning
confidence: 99%
“…Sustainable precipitation of carbonate minerals may provide green means of mitigating some geotechnical challenges associated with soils. Microbial-induced carbonate precipitation (MICP) and CO 2 -induced carbonate precipitation (CICP) can induce interparticle cementation and mineral precipitation in soil pore space to address geotechnical problems such as soil erosion and slope instability (Keykha et al 2017, Keykha et al 2018a, Romiani et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…e deposition of CaCO 3 increases as the concentration of cementation solution increases, but there are differences in the optimal cementation schemes, such as [41,48,50] (Figure 4). According to the research results of [49,51], the maximum deposition of CaCO 3 occurs in cement solutions with high Ca 2+ concentration. erefore, the cementation solution significantly influences the bacterial activity, CaCO 3 precipitation, and soil cementation in MICP (Table 1).…”
Section: Cementation Solution Concentrationmentioning
confidence: 99%